Makna dan Nilai Ubo Rampe pada Tradisi Brokohan Sapi di Desa Tempursari Kecamatan Donomulyo Kabupaten Malang - Susita Rahayu; Daroe Iswatiningsih (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
The Brokohan Sapi tradition in Tempursari Village, Donomulyo District, Malang Regency represents a form of local wisdom that embodies cultural and symbolic values through the use of ubo rampe. This study aims to describe the forms, meanings, and cultural values of ubo rampe in the Brokohan Sapi tradition. The study employs a qualitative method with a symbolic anthropological approach as proposed by Clifford Geertz. Data were collected through observation, interviews, and documentation, and were analyzed using an interactive analysis technique involving data reduction, data display, and conclusion drawing. The findings reveal that ubo rampe is systematically arranged in the form of food offerings, including core dishes, complementary dishes, and spiritual elements. Each component of ubo rampe carries symbolic meanings related to gratitude, safety, fertility, and hopes for prosperity. The cultural values embedded in the tradition include religious, social, ecological, economic, and philosophical values that are integrated into ritual practices. The implications of this study indicate that the Brokohan Sapi tradition functions as a medium for cultural preservation and can be utilized as a local wisdom-based learning resource in Indonesian language and literature education.